Pelatihan Pemanfaatan Pinterest for Business bagi Pelaku UMKM di Kompleks Mawar Permai Kabupaten Kubu Raya - Budi Susilo (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
Many housewives in RT 04/RW 13 of the Mawar Permai Complex, Kubu Raya Regency, operate micro-scale home-based businesses; however, their product promotion still relies on conventional word-of-mouth methods and WhatsApp status updates, resulting in limited market reach. The partners were previously unfamiliar with Pinterest a visual-based social media platform with significant potential for showcasing product catalogs and directing potential buyers to sales channels. This community service activity aimed to enhance the partners' understanding and practical skills in utilizing Pinterest for Business as a digital promotion tool. The implementation method involved a workshop comprising preparation, interactive lectures, demonstrations, and hands-on guidance for creating business accounts, boards, and product pins, attended by 15 participants. Success was measured using pre- and post-test instruments containing ten comprehension questions, alongside a participant satisfaction survey. The results showed an increase in the average comprehension score from 44.33 (pre-test) to 81.00 (post-test) an 82.7% increase with an average N-Gain score of 0.67 (categorized as medium-to-high). Participant satisfaction regarding the activity reached 90.9%. These results indicate that hands-on, practice-based training is effective in improving visual digital marketing literacy among home-based MSME operators.